Transformational Leadership as a Strategy to Improve the Quality of Education in Islamic Boarding Schools - Akhmad Fauzi Hamzah; Ahmad Shomadi (Institut Attanwir Bojonegoro, 2025)
This study discusses the implementation of transformational leadership strategies in improving the quality of education at the Darussalam Jatibarang Islamic Boarding School, Brebes. Transformational leadership is seen as relevant to the needs of modern Islamic boarding schools because it is not only instruction-oriented, but also acts as a motivator, innovator, and morality coach. This study uses a qualitative approach with a case study method through observation, in-depth interviews, and documentation validated by triangulation of sources. The results of the study show that transformational leadership in the Darussalam Islamic Boarding School plays a significant role in strengthening vision, professionalizing management, improving the quality of human resources, and spiritual and intellectual development. The strategies implemented include organizational restructuring, regeneration, strengthening networking, quality culture, and financial transparency. The analysis shows that transformational leadership in this pesantren is in line with Bass' theory (idealized influence, inspirational motivation, intellectual stimulation, individualized consideration) and is rooted in Qur'anic values and Islamic prophetic traditions. These findings confirm that transformational leadership can be an effective model in developing the quality of Islamic education, especially in Islamic boarding schools, so that it is able to answer the challenges of modernization without abandoning Islamic identity.